2015
DOI: 10.2308/acch-51262
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Analysis of Accounting Professionals' Work-Life Balance

Abstract: SYNOPSIS In recent years, work-life balance surpassed compensation as the most important job satisfaction factor among AICPA members (American Institute of Certified Public Accountants [AICPA] 2004). Despite the continued importance of this issue in the accounting profession (AICPA 2011), prior research has not examined work-life balance perceptions across different segments of the profession. We survey 1,063 practicing CPAs in order to assess the comparative work-life balance perceptions across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 60 publications
5
96
1
2
Order By: Relevance
“…As early as 1982, Maslach asserted that organizations should be cognizant of burnout symptoms among employees because there is often a negative relationship between burnout and performance (Maslach 1982). A number of studies have found that excessive workload can cause employees to experience burnout -emotional exhaustion, depersonalization, and reduced personal accomplishment (Rose 1983;Sanders 1998;Fogarty et al 2000;Almer and Kaplan 2002;Sweeney and Summers 2002;Jones, Norma, and Wier 2010;Herda and Lavelle 2012;Buchheit et al 2016). McKee (2014) explains that negative emotions experienced at work, often associated with burnout, lead people to not "process information as well, think creatively, or make good decisions.…”
Section: Audit Workloads: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1982, Maslach asserted that organizations should be cognizant of burnout symptoms among employees because there is often a negative relationship between burnout and performance (Maslach 1982). A number of studies have found that excessive workload can cause employees to experience burnout -emotional exhaustion, depersonalization, and reduced personal accomplishment (Rose 1983;Sanders 1998;Fogarty et al 2000;Almer and Kaplan 2002;Sweeney and Summers 2002;Jones, Norma, and Wier 2010;Herda and Lavelle 2012;Buchheit et al 2016). McKee (2014) explains that negative emotions experienced at work, often associated with burnout, lead people to not "process information as well, think creatively, or make good decisions.…”
Section: Audit Workloads: Previous Researchmentioning
confidence: 99%
“…However, while role conflict was found to be significantly lower among CPAs under a flexible work arrangement, neither role ambiguity nor role overload was significantly influenced by flexible work arrangements. In addition, Buchheit et al (2016), in a study examining accounting professionals' work-life balance, find that while audit, tax, and industry accountants report similar levels of support for alternative work arrangements (AWAs), Big 4 professionals report significantly lower perceived viability of these arrangements.…”
Section: Audit Workloads: Previous Researchmentioning
confidence: 99%
“…But instead of getting this support, some people may demand they prioritize their family time. This unsupported condition also causes an imbalance between their work and family responsibilities (Buchheit et al 2016). In other words, the work-family conflict exists in two dimensions, that is when work is interfering with family responsibilities and/or the family is interfering with work responsibilities (Pasewark and Viator 2006;Beutell 201).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are concerns about the day-to-day workload and the predictability of one's schedule. Buchheit, Dalton, Harp, and Hollingsworth (2016) examine work-life balance and alternative work arrangements (i.e., flextime, part-time work, telecommuting, and compressed workweeks) in public accounting and industry. They find that work-life challenges are most acute in the Big 4 firms.…”
Section: Selected Recent Researchmentioning
confidence: 99%